2019
DOI: 10.1371/journal.pone.0214764
|View full text |Cite
|
Sign up to set email alerts
|

RalA and RalB relocalization to depolarized mitochondria depends on clathrin-mediated endocytosis and facilitates TBK1 activation

Abstract: Healthy mitochondria use an electrochemical gradient across the inner mitochondrial membrane (IMM) to generate energy in the form of ATP. A variety of endogenous and exogenous factors can lead to transient or sustained depolarization of the IMM, including mitochondrial fission events, expression of uncoupling proteins, electron transport chain (ETC) inhibitors, or chemical uncouplers. This depolarization in turn leads to a variety of physiological responses, ranging from selective mitochondrial clearance (mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…However, the mitochondrial fragmentation induced by L. monocytogenes is Drp1 independent and does not result in mitochondrial redistribution to polarized structures (Stavru et al, 2011(Stavru et al, , 2013. Interestingly, a recent report showed that endocytosis-dependent relocalization of the small GTPases RalA and RalB to depolarized mitochondria plays an important role in innate immune signaling (Pollock et al, 2019). Whether L. monocytogenes interferes with similar mechanisms is currently unclear, and future work will be needed to characterize the interplay between mitochondrial energy metabolism, endocytic recycling, and infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mitochondrial fragmentation induced by L. monocytogenes is Drp1 independent and does not result in mitochondrial redistribution to polarized structures (Stavru et al, 2011(Stavru et al, , 2013. Interestingly, a recent report showed that endocytosis-dependent relocalization of the small GTPases RalA and RalB to depolarized mitochondria plays an important role in innate immune signaling (Pollock et al, 2019). Whether L. monocytogenes interferes with similar mechanisms is currently unclear, and future work will be needed to characterize the interplay between mitochondrial energy metabolism, endocytic recycling, and infection.…”
Section: Discussionmentioning
confidence: 99%
“…During mitochondrial fission, phosphorylation by the kinase Aurora A leads to activation of RalA and its relocation to the mitochondrial outer membrane, while RalB is unaffected. [3,4] More recently, it was found that mitochondrial depolarisation triggers both RalA and RalB to relocate to mitochondria, [2] releasing RalB inhibition of TANK-binding kinase 1 (TBK1) at the plasma membrane, which is necessary for mitophagy. [17] While the relocation of RalA/B in response to mitochondrial depolarisation is dependent on clathrin mediated endocytosis, [2] no mechanism of transport has been suggested for RalA-specific trafficking to mitochondria during fission.…”
Section: Functional Consequences For Mitochondrial Dynamicsmentioning
confidence: 99%
“…[3,4] More recently, it was found that mitochondrial depolarisation triggers both RalA and RalB to relocate to mitochondria, [2] releasing RalB inhibition of TANK-binding kinase 1 (TBK1) at the plasma membrane, which is necessary for mitophagy. [17] While the relocation of RalA/B in response to mitochondrial depolarisation is dependent on clathrin mediated endocytosis, [2] no mechanism of transport has been suggested for RalA-specific trafficking to mitochondria during fission. We speculate that CaM acts as an RalA-specific chaperone, shuttling RalA to the mitochondrial outer membrane.…”
Section: Functional Consequences For Mitochondrial Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…TBK1 phosphorylates OPTN at Ser177 to promote its interaction with ATG8/LC3 proteins [370] and at Ser473 and Ser513 to confer it with the ability to bind to the ubiquitin chain [371][372][373]. In addition, TBK1-mediated autophosphorylation, p62/SQSTM1 phosphorylation at Ser403, Rab7 phosphorylation at Ser72, and other phosphorylation events have been shown to regulate mitophagy [266,[374][375][376]. A recent study also noted that the Ca 2+ -binding protein TBC1 domain family member 9 (TBC1D9) may induce mitophagy by activating TBK1 [377].…”
Section: Phosphorylation and Dephosphorylationmentioning
confidence: 99%